APPLICATION OF THE FORWARD CHAINING METHOD IN DOWN SYNDROME PATIENTS - kurniati . (Faculty of Computer Science - Universitas Indonesia, 2019)
According to WHO data, the incidence of Down syndrome is 1 in 1,000 live births in the world. Down syndrome is a backward condition in the physical and mental development of children that results from abnormal chromosome development. However, these conditions are often too late to be realized by the parents of the sufferer. By conducting this study using the forward chaining method aims to help parents to do early detection of the level of retardation of Down syndrome. So, with the existence of this application, it is very petrifying for parents to carry out treatment from an early age in the right way. Thus, sufferers of dwon syndrome get maximum support and attention from the people closest and nearby so that children with dwon syndrome can grow happily and have a decent life like other normal children even though this dwon syndrome cannot be cured.